2015
DOI: 10.2967/jnumed.115.159012
|View full text |Cite
|
Sign up to set email alerts
|

MIRD Pamphlet No. 26: Joint EANM/MIRD Guidelines for Quantitative 177Lu SPECT Applied for Dosimetry of Radiopharmaceutical Therapy

Abstract: The accuracy of absorbed dose calculations in personalized internal radionuclide therapy is directly related to the accuracy of the activity (or activity concentration) estimates obtained at each of the imaging time points. MIRD Pamphlet no. 23 presented a general overview of methods that are required for quantitative SPECT imaging. The present document is next in a series of isotope-specific guidelines and recommendations that follow the general information that was provided in MIRD 23. This paper focuses on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
273
1
17

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 270 publications
(297 citation statements)
references
References 58 publications
6
273
1
17
Order By: Relevance
“…Zoom of 1, circular radius of rotation of 330 mm (around the phantom surface) and image matrix of 128x128 pixels were set, resulting in a 4.8 mm pixel size image. In acquisition, the energy windows of the two dominant photopeaks of 177 Lu [4] were set at 113keV ± 7.5% and 208.4keV ± 7.5%, as also described in Grassi et al [30]. As regards the lower energy photopeak, the TEW scatter correction was employed and the lower scatter window was set in the range from 87.58keV to 104.53keV (using a default window weight of 0.5), while the upper scatter window from 121.47keV to 130.51keV (using a default window weight of 0.9375).…”
Section: Spect/ct Acquisition and Reconstructionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zoom of 1, circular radius of rotation of 330 mm (around the phantom surface) and image matrix of 128x128 pixels were set, resulting in a 4.8 mm pixel size image. In acquisition, the energy windows of the two dominant photopeaks of 177 Lu [4] were set at 113keV ± 7.5% and 208.4keV ± 7.5%, as also described in Grassi et al [30]. As regards the lower energy photopeak, the TEW scatter correction was employed and the lower scatter window was set in the range from 87.58keV to 104.53keV (using a default window weight of 0.5), while the upper scatter window from 121.47keV to 130.51keV (using a default window weight of 0.9375).…”
Section: Spect/ct Acquisition and Reconstructionmentioning
confidence: 99%
“…Several investigations have been reported on the performance of such algorithm on radionuclides frequently used in nuclear medicine, for patient imaging as well as patient specific dosimetry. Some of the more pertinent publications include improvements in correction techniques for quantification in SPECT [4,[17][18][19][20], evaluations of the accuracy of quantitative image reconstruction techniques [21][22][23][24][25] and comparisons of resolution between SPECT/CT systems using machine-specific reconstruction algorithms [26][27][28]. In these studies, the OSEM reconstruction parameters (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…From the results of this work, it can be concluded that PLA-based FDM 3D printing along with an epoxy coating enables the production of chemically stable, fillable phantoms that are sufficiently durable for SPECT/CT calibration studies. Although no significant differences in partial-volume effects were found between the kidney-shaped and the spherically shaped single-compartment phantoms, this conclusion will have to be reevaluated for more realistic kidney geometries, in which a low-activity inner region is typically surrounded by a ring of higher activity (5).…”
Section: Limitations Of and Possible Improvements To Single-compartmementioning
confidence: 99%
“…Peritherapeutic dosimetry in molecular radiotherapies with 177 Lu-labeled compounds, although sometimes limited by the availability of patients for late-time-point measurements, can be easily performed with limited technical difficulties (54). Most importantly, the demonstration of a tumor dose-response relationship (42) and the observation of minimal differences between cycles (12,41) indicate that posttherapeutic dosimetry after a first treatment cycle predicts the absorbed doses in further cycles.…”
Section: Individualized Dosimetry: Necessary Nice To Have or Countementioning
confidence: 99%